Identification of protein interaction partners by the yeast two-hybrid system - Garcia-Cuellar, Maria-Paz; Mederer, Deniz; Slany, Robert (2009)
The two-hybrid system is a genetic method to search for and to identify direct interaction partners of a protein of interest. This method is instrumental to elucidate the transformation mechanism of several oncogenes that play a role in childhood leukaemia. With respect to mixed lineage leukaemia gene (MLL) fusions, two-hybrid screening was applied to discover proteins that bind to various MLL fusion partners. Here we describe a streamlined protocol that enables any average molecular biology laboratory to conduct and evaluate a standard two-hybrid screen. Starting with a general explanation of the biological background of the two-hybrid method, this chapter covers the construction of bait vectors and two comprehensive protocols for screening either by yeast mating or yeast transformation. In addition, it also gives guidelines for the evaluation of two-hybrid results. © 2009 Humana Press, a part of Springer Science+Business Media, LLC.
Keywords: MLL fusion partner; Protein-protein interaction; Two-hybrid screening